Host and symbiont genetic determinants of nutritional phenotype in a natural population of the pea aphid. Issue 4 (27th January 2020) - Chung, Seung Ho; Parker, Benjamin J.; Blow, Frances; Brisson, Jennifer A.; Douglas, Angela E.
Abstract: A defining feature of the nutritional ecology of plant sap‐feeding insects is that the dietary deficit of essential amino acids (EAAs) in plant sap is supplemented by EAA‐provisioning microbial symbionts in the insect. Here, we demonstrated substantial variation in the nutritional phenotype of 208 genotypes of the pea aphid Acyrthosiphon pisum collected from a natural population. Specifically, the genotypes varied in performance (larval growth rates) on four test diets lacking the EAAs arginine, histidine and methionine or aromatic EAAs (phenylalanine and tryptophan), relative to the diet containing all EAAs. These data indicate that EAA supply from the symbiotic bacteria Buchnera can meet total aphid nutritional demand for only a subset of the EAA/aphid genotype combinations. We then correlated single nucleotide polymorphisms (SNPs) identified in the aphid and Buchnera genomes by reduced genome sequencing against aphid performance for each EAA deletion diet. This yielded significant associations between performance on the histidine‐free diet and Buchnera SNPs, including metabolism genes predicted to influence histidine biosynthesis. Aphid genetic correlates of performance were obtained for all four deletion diets, with associations on the arginine‐free diet and aromatic‐free diets dominated by genes functioning in the regulation of metabolic and cellular processes. The specific aphid genes associated with performance on different EAA deletion diets are largely nonoverlapping, indicating some independence in the regulatory circuits determining aphid phenotype for the different EAAs. This study demonstrates how variation in the phenotype of associations collected from natural populations can be applied to elucidate the genetic basis of ecologically important traits in systems intractable to traditional forward/reverse genetic techniques.